(untitled) (Communications in Computational Physics, 2018)
In some superconductors the charge density wave (CDW) state is adjacent to the superconducting state in the phase diagram. This CDW phase can be collapsed either pressure or by chemical doping, depending on compound. Among them, in so-called valence skip compounds, a large charge fluctuation with the large electron-phonon interaction is expected. We performed a first-principle study and investigated how the CDW gap is collapsed for several valence-skip compounds, i.e. SnX3, RbTlX3(X=F,Cl,Br,I) and CsTlI3. For all these compounds we found that the CDW gap is rather robust for the uniform volume change, and on the contrary, the magnitude of the CDW gap strongly depends on the position of the anion. We found that this CDW gap is already collapsed at ambient pressure in SnBr3, SnI3 and CsTlI3.